Obesity as Type 2 Diabetes Common Comorbidity: Study of Type 2 Diabetes Patients’ Eating Behaviour and Other Determinants in Jakarta, Indonesia - Fajarini, Isna Aulia; Sartika, Ratu Ayu Dewi (Kesmas, 2019)
Obesity is one of the comorbidities widely occurred among type 2 diabetes patients. It is one of the most modifiable risk factors for the prevention of other comorbid conditions such as diabetic nephropathy and cardiovascular disease. The aim of this study was to recognize eating behaviour, physical activity, and other related factors, also their correlation with obesity as comorbidity among type 2 diabetes patients. Using cross-sectional design, data were collected from purposively selected 133 members of “PROLANIS” in Jatinegara Primary Health Care, East Jakarta. Food intake was assessed by 1x24 hours food recall and FFQ, physical activity by GPAQ. The result showed 63,9% of adult with type 2 diabetes were obese (BMI ≥25 kg/m2), fat intake was higher than recommendation (30,77±9,06%), but mean energy intake was insufficient compared to energy requirement (62,06±23,67%). The prevalence of obesity among adults with type 2 diabetes is found associated with nutrition knowledge, level of education, and length of suffering type 2 diabetes. Nutrition education is important to reduce the prevalence of obesity among adults with type 2 diabetes.